Why are reactions of 2‐ and 8‐thioquinoline derivatives with iodine different?. Issue 8 (26th July 2018) - Rudakov, Boris V.; Stash, Adam I.; Makarov, Gennady I.; Matveychuk, Yury V.; Zherebtsov, Dmitry A.; Bartashevich, Ekaterina V.
Abstract : The reaction of 1, 4‐bis(quinolin‐2‐ylsulfanyl)but‐2‐yne with iodine leads to two different single crystals, namely the dimonoiodide hemihydrate and the monoiodide triiodide of the 1, 2‐dihydro‐1, 1′‐bi[thiazolo[3, 2‐ a ]quinoline]‐10a, 10a′‐diium dication. Interaction of the iodide anions with the dication takes place through chalcogen bonds. Abstract : The crystal structures of 1, 2‐dihydro‐1, 1′‐bi[thiazolo[3, 2‐ a ]quinoline]‐10a, 10a′‐diium diiodide hemihydrate, C22 H16 N2 S2 2+ ·2I − ·0.5H2 O, and 1, 2‐dihydro‐1, 1′‐bi[thiazolo[3, 2‐ a ]quinoline]‐10a, 10a′‐diium iodide triiodide, C22 H16 N2 S2 2+ ·I − ·I3 −, obtained during the reaction of 1, 4‐bis(quinolin‐2‐ylsulfanyl)but‐2‐yne (2TQB) with iodine, have been determined at 120 K. The crystalline products contain the dication as a result of the reaction proceeding along the iodocyclization pathway. This is fundamentally different from the previously observed reaction of 1, 4‐bis(quinolin‐8‐ylsulfanyl)but‐2‐yne (8TQB) with iodine under similar conditions. A comparative analysis of the possible conformational states indicates differences in the relative stabilities and free rotation for the 2‐ and 8‐thioquinoline derivatives which lead to a disparity in the convergence of the potential reaction centres for 2TQB and 8TQB.